War, International Spillovers, and Adolescents: Evidence from Russia's Invasion of Ukraine in 2022 - Thomas Siedler; Silke Anger; Bernhard Christoph; Agata Galkiewicz; Shushanik Margaryan; Frauke Peter; Malte Sandner (Institute of Labor Economics (IZA), 2024)
Using novel longitudinal data, this paper studies the short- and medium-term effects of Russia's invasion of Ukraine on February 24, 2022 on social trust of adolescents in Germany. Comparing adolescents who responded to our survey shortly before the start of the war with those who responded shortly after the conflict began and applying difference-in-differences (DiD) models over time, we find a significant decline in the outcome after the war started. These findings provide new evidence on how armed conflicts influence social trust and well-being among young people in a country not directly involved in the war.
Keywords: C23; H75; I14; N44; 330; war; trust; social capital; Russia's invasion of Ukraine